Experiences of piloting integrated bite case management in Zaria Metropolis, Nigeria - Kia, Grace Sabo Nok; Samuel, Mathias; Ferguson, Elaine A.; Ibrahim, Ishaq; Lushasi, Kennedy; Okpanachi, Jerome; Chng, Nai Rui; Kwaga, Jacob Kwada Paghi; Hampson, Katie (Frontiers in Tropical Diseases, 2026)
BackgroundRabies remains a major public health risk in Africa and is estimated to cause over 1,600 deaths annually in Nigeria. Integrated Bite Case Management (IBCM) is recommended as a One Health approach for rabies surveillance but has yet to be implemented within Nigeria.MethodsOur aim was to gain epidemiological and operational understanding of implementing IBCM within Sabon Gari Local Government Area (LGA) of Zaria Metropolis, Kaduna State, Nigeria through an implementation research approach. We developed an IBCM protocol with local practitioners and piloted it from April 2023 until December 2024, and analyzed resulting data.ResultsWe identified very low access to rabies post-exposure prophylaxis (PEP) within the study area. Although incidence of bite patients was low (~0.98/100,000/year, 95% confidence intervals, CI: 0.68-1.42), a large proportion were identified as rabies exposures (41%) and two human rabies deaths occurred (0.11 deaths/100,000/year, 95%CI: 0.031-0.41), corresponding to very low healthcare seeking (0.50 probability of rabies exposures receiving PEP, 95%CI: 0.27-0.86). Investigations triggered by dog bite incidents or community notifications identified probable rabid dogs from clinical signs/history (45% of investigated dogs), with all recoverable samples (8) confirmed positive by rapid testing, including three dogs that died in quarantine. IBCM revealed the dog meat trade as a sentinel for rabies detection, with three rabid dogs sold for consumption. Key aspects of IBCM were refined to improve implementation during the pilot.ConclusionsPiloting IBCM revealed a low incidence of bite presentations reflecting the small dog population (high human: dog ratio) in these communities and very low levels of care seeking among those at risk. We conclude that there is an urgent need to simultaneously improve PEP access and raise awareness about the dangers of rabies. Other critical gaps in rabies control and prevention, include low dog vaccination coverage, limited training in rabies prevention and a lack of resources for surveillance, despite urgent demand and enthusiasm for implementation. The generalizability of our conclusions are limited given our experiences are derived from a single LGA. Nevertheless, this we provide lessons for how to develop IBCM for this local health and veterinary context in accordance with cultural norms and identify considerations for the design and implementation of IBCM elsewhere.